Trust And Commitment In Maintaining Marriage Among Teachers In Commuting Marriage In Kota Kinabalu Sabah - Joki Perdani Sawai; Mahirah Masdin; Balan Rathakrishnan; Syaidatun Nazirah Abu Zahrin; Rezki Perdani Sawai (Human Research Management Academic Research Society, 2024)
Indexed by ERA